(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Glioblastoma (GBM) is the most aggressive primary brain tumor, causing neurological symptoms and requiring MRI-guided surgery followed by radiotherapy and temozolomide. Despite treatment, prognosis remains poor, with a median survival of about 14 months, though outcomes improve with younger age, maximal safe resection, and completion of therapy. Advanced imaging may improve prognostic assessment, but data from low-resource settings remain limited. Methods: A 5-year forward-looking study (2021–2026) at Dhaka Medical College Hospital and Green Life Hospital involved 30 patients with supratentorial glioblastoma who underwent maximal safe resection along with standard chemoradiotherapy. Patients underwent clinical and MRI evaluations, and survival analysis was conducted using the Kaplan–Meier method. Approval from the ethics committee and informed consent were secured Results: Fifteen patients diagnosed with supratentorial glioblastoma (average age 54.2 years) primarily exhibited headaches, seizures, and focal deficits. The majority had frontal tumors, lesions that did not cross the midline, and received gross total resection followed by chemoradiotherapy. The median overall survival time was 16.4 months, and the 5-year survival rate was 20% (6 out of 30). Improved outcomes were linked to gross total resection, tumors located away from the midline, completion of treatment, and positive MRI characteristics Conclusion: Supratentorial glioblastoma has a grim outlook even with combined treatment approaches. Improved survival correlates with gross total resection, thorough chemoradiotherapy, non-midline tumor positioning, and positive MRI characteristics, emphasizing the significance of extensive safe surgery and advanced imaging for predicting outcomes. Journal of Paediatric Surgeons of Bangladesh (2026) Vol. 17 (1): 73-77